Consensually Defined Facets of Personality as Prospective Predictors of Change in Depression Symptoms. (August 2014) - Naragon-Gainey, Kristin; Watson, David
Depression has robust associations with personality, showing a strong relation with neuroticism and more moderate associations with extraversion and conscientiousness. In addition, each Big Five domain can be decomposed into narrower facets. However, we currently lack consensus as to the contents of Big Five facets, with idiosyncrasies across instruments; moreover, few studies have examined associations with depression. In the current study, community participants completed six omnibus personality inventories; self-reported depressive symptoms were assessed at baseline and 5 years later. Exploratory factor analyses suggested three to five facets in each domain, and these facets served as prospective predictors of depression in hierarchical regressions, after accounting for baseline and trait depression. In these analyses, high anger (from neuroticism), low positive emotionality (extraversion), low conventionality (conscientiousness), and low culture (openness to experiences) were significant prospective predictors of depression. Results are discussed in regard to personality structure and assessment, as well as personality–psychopathology associations.